The value of clinical routine blood biomarkers in predicting long-term mortality after stroke. (June 2023) - Hatab, Isra; Kneihsl, Markus; Bisping, Egbert; Rainer, Peter P; Fandler-Höfler, Simon; Eppinger, Sebastian; Haidegger, Melanie; Berger, Natalie; Mangge, Harald; Schmidt, Reinhold; Enzinger, Christian; Gattringer, Thomas
Background: Several blood biomarkers have been identified as predictors for poor outcome after ischemic stroke. However, recent studies mainly focused on single or experimental biomarkers and considered rather short follow-up intervals limiting their value for daily clinical practice. We, therefore, aimed to compare various clinical routine blood biomarkers for their predictive value on post-stroke mortality over a 5-year follow-up period. Patients and methods: This data analysis of a prospective single-center study included all consecutive ischemic stroke patients admitted to the stroke unit of our university hospital over a 1-year period. Various blood biomarkers of inflammation, heart failure, metabolic disorders, and coagulation were analyzed from standardized routine blood samples collected within 24 h of hospital admission. All patients underwent a thorough diagnostic workup and were followed for 5 years post-stroke. Results: Of 405 patients (mean age: 70.3 years), 72 deceased (17.8%) during the follow-up period. While various routine blood biomarkers were associated with post-stroke mortality in univariable analyses, only NT-proBNP remained an independent predictor (adjusted odds ratio 5.1; 95% CI 2.0–13.1; p < 0.001) for death after stroke. NT-proBNP levels ⩾794 pg/mL ( n = 169, 42%) had a sensitivity of 90% for post-stroke mortality with a negative predictive value of 97% and was additionally associated with cardioembolic stroke and heart failure (each p ⩽ 0.05). Conclusion: NT-proBNP represents the most relevant routine blood-based biomarker for the prediction of long-term mortality after ischemic stroke. Increased NT-proBNP levels indicate a vulnerable subgroup of stroke patients in which early and thorough cardiovascular assessment and consistent follow-ups could improve outcome after stroke.